How much does your building weigh, Mr. Foster? [videorecording (DVD)] - López Amado, Norberto, 1965-; Carcas, Carlos; Sudjic, Deyan; Foster, Norman, 1935-; Fuller, R. Buckminster (Richard Buckminster), 1895-1983; Rogers, Richard, 1933-; Kapoor, Anish, 1954-; Serra, Richard, 1938-; Caro, Anthony, 1924-2013; Long, Richard, 1945-; Bono, 1960- (First Run Features, 2012)
Born in Manchester, England on the wrong side of the tracks, Norman Foster rose from a humble working class background to become one of the premiere architects of modern times. Beautifully filmed in over ten countries and homing in on his most iconic works, including London's Swiss Re Tower, New York's Hearst Building, Berlin's Reichstag, and more, it's an unprecedented exploration of an architect whose quest is to improve the quality of life through design.